Сlinical features of malignant tumors against the background of immunosuppressive therapy in heart transplant recipients - L. B. Krougly; N. N. Koloskova; A. V. Nikulin; I. V. Pashkov; V. N. Poptsov; A. O. Shevchenko (Вестник трансплантологии и искусственных органов)
As the survival rate of cardiac recipients improves, higher incidence of malignancy in the late postoperative period becomes essential for their prognosis. Immunosuppressive therapy is one of the key prerequisites for successful transplantation. However, long-term use of immunosuppressive agents increases the incidence of malignant tumors compared to the general population. The risk of their development after organ transplantation increases by 2–4 times compared to the general population. For patients who have undergone transplantation since 2000, the risk of developing malignant neoplasms 1–5 years after surgery is estimated at 10–12%. Timely comprehensive examination of patients, development of new immunosuppression schemes, treatment of those predisposing to the development of malignant neoplasms and giving up harmful habits will reduce the risk of malignant tumors and help diagnose these serious complications at an early stage, which, in turn, will increase the life expectancy of solid organ (particularly the heart) recipients.